Towards a Model-Based Experimental Design of the Maturation Process of Biohybrid Heart Valves. Issue 26 (2019) - Voß, Kirsten; Pyta, Lorenz; Gesenhues, Jonas; Mela, Petra; Schmitz-Rode, Thomas; Abel, Dirk
Abstract: Model-based experimental designs minimize the experimental effort while maximizing the amount of analyzable experimental data. In this paper, an initial mathematical model of the spatially distributed maturation process of tissue engineered heart valves is developed for a model-based experimental design. The model contains the state variables cell amount, collagen concentration and elastin concentration. Based on the developed model, a variance-based sensitivity analysis using Sobol's method is performed. The results indicate that all model parameters influence the model solution, while the variance of the parameters related to cell diffusion comprises an exceeding influence. Consequently, corresponding experiments should especially focus on those parameters.